EKSTERNALITAS NEGATIF PENGGUNAAN TRANSPORTASI PRIBADI DI KOTA BANDA ACEH - M. Harish; Diana Sapha A.H. (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to find out and analyze the impact of the use of private transportation on negative externalities in the city of Banda Aceh. The data used in this study are primary data and secondary data, primary data obtained by giving questionnaires to 100 respondents of private transport users in Banda Aceh City. The method used in this study is descriptive qualitative and quantitative descriptive analysis. There is a significant relationship between the variables of education, employment income, the number of vehicles and distance to the willingness of the community to pay costs so that negative externalities are reduced in Banda Aceh. the greater the costs that the community is willing to pay. Based of these findings, it is expected that further researchers are advised to examine the effect of transportation financing on student achievement indexes.Keywords: Negative Externalities, Users of Private Transportation, Users of Public Transportation, Qualitative Analysis, Quantitative Analysis.